Analysis of a HT-PEMFC range extender for a light duty full electric vehicle (LD-FEV). (5th October 2016) - Millo, F.; Caputo, S.; Piu, A.
Abstract: The usage of a Fuel Cell (FC) as a range extender in a Full Electric Vehicle (FEV) is a convenient solution to address the issue of the shortage of range of this type of vehicles. Compared with the Internal Combustion Engine – Range Extender (ICE-RE), the Fuel Cell – Range Extender (FC-RE) has the potential to provide power with higher efficiency (more than 50%) and, above all, it can allow zero emissions operation of the vehicle even when the on-board power source is switched on for range extension. In this work, the introduction of a new HT-PEMFC (High Temperature–Proton Exchange Membrane Fuel Cell), developed in the framework of the collaborative European project ARTEMIS (A utomotive pemfcR ange extender with highTEM peratureI mproved meas andS tacks), on a light duty, full electric, commercial vehicle, was investigated. Firstly, a model of the Full Electric Vehicle was created and validated by means of experimental tests carried out on rolling chassis dyno over both type approval and real world driving cycles. Once the model was developed, the effects of the introduction of an HT-PEMFC on the vehicle range was evaluated and the performances of different HT-PEM fuel cell stack systems, combined with various hydrogen storage system configurations, were compared. Highlights: Analysis of a high temperature PEM Fuel Cell used as a Range Extender for a Full Electric Vehicle. Assessment of its performance through numerical simulation of real world operating conditions. Increase of the vehicle range of 19% over a real world urban driving cycle highlighted.